Psychosocial Problem among School-going Adolescents in Pokhara, Western Nepal - Banstola, Ratna Shila (Janapriya Journal of Interdisciplinary Studies, 2018)
Adolescence the second decade of life is the crucial period demanding significant adjustment to the physical and social changes. During this transitional period, if adequate care and attention is not given adolescents are prone to develop various psychosocial problems with long standingimpact. This descriptive cross-sectional study was conducted to assess the prevalence of psychosocial problem and its associated factors among 360 adolescents studying in public schools of Pokhara Lekhnath Metropolitan City. Data was collected by using self-administered questionnaire. The data was analyzed in SPSS version 16 applying both descriptive and inferential statistics. Findings of the study revealed that 21.7 percent of adolescents had psychosocial problem. Adolescents who are facing physical/verbal abuse (p=0.000, OR: 13.54),who do not feel good about home environment (p=0.000, OR: 5.01), have high academic/school relates stress (p=0.000, OR:5.304), who do not stay with their parents (p=0.000, OR: 4.49), belonged to hardly sufficient family income (p=0.000, OR: 3.29), those from joint family (p=0.004, OR: 2.12), whose mothers are illiterate (p=0.027, OR: 1.96) and having disrupted marital status of parents (p=0.040, OR: 1.78) were more likely to have psychosocial problem. Hence, the combined effort of family and school team is essential to protect adolescents from developing psychosocial problem. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017), page: 121-133